2016
DOI: 10.1007/s10584-016-1708-z
|View full text |Cite
|
Sign up to set email alerts
|

Detection of anthropogenic influence on a summertime heat stress index

Abstract: One of the most consequential impacts of anthropogenic warming on humans may be increased heat stress, combining temperature and humidity effects. Here we examine whether there are now detectable changes in summertime heat stress over land regions. As a heat stress metric we use a simplified wet bulb globe temperature (WBGT) index. Observed trends in WBGT (1973WBGT ( -2012) are compared to trends from CMIP5 historical simulations (eight-model ensemble) using either anthropogenic and natural forcing agents comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
63
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 31 publications
9
63
0
3
Order By: Relevance
“…The influence of anthropogenic forcings (i.e., ANT, GHG, or OANT) is clearly detectable in the observed summer WBGT, but the influence of NAT is not detected (Figure c). This is consistent with Knutson and Ploshay (). The best estimate of the scaling factor for ANT is slightly larger than one but the 90% uncertainty range of scaling factor includes one (pink bar in Figure c), suggesting that the modeled response to ANT may be somewhat underestimated but it is still consistent with the observations.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The influence of anthropogenic forcings (i.e., ANT, GHG, or OANT) is clearly detectable in the observed summer WBGT, but the influence of NAT is not detected (Figure c). This is consistent with Knutson and Ploshay (). The best estimate of the scaling factor for ANT is slightly larger than one but the 90% uncertainty range of scaling factor includes one (pink bar in Figure c), suggesting that the modeled response to ANT may be somewhat underestimated but it is still consistent with the observations.…”
Section: Resultssupporting
confidence: 92%
“…This trend pattern is similar, in terms of both spatial distribution and magnitude, to that of summer air temperature ( Figure S2a), suggesting that the widespread intensification of summer WBGT is largely a result of rising summer temperatures. This is consistent with Knutson and Ploshay (2016) who found that the global mean summer WBGT trend changes little if fixed climatological RH was used to compute WBGT. In fact, RH trend is small across the covered land ( Figure S2b).…”
Section: Observation-constrained Projectionssupporting
confidence: 91%
See 1 more Smart Citation
“…However, the challenge is that the traditional approach to attribution is intractable for any single heat event. It can be used, however, on climatologies of heat events or indices (e.g., [94]). …”
Section: Attribution Of Recent Eventsmentioning
confidence: 99%
“…The water vapor capacity of air is largest in high temperatures, and accordingly, the impacts of RH have been studied most widely in warm conditions. To mention some examples, RH contributes to the growth of crops [e.g., Asseng et al, 2015], human comfort and heat stress [e.g., Willett and Sherwood, 2012;Knutson and Ploshay, 2016], wildfires [e.g., Lehtonen et al, 2014;Vajda et al, 2014], and surface evapotranspiration and soil moisture [e.g., Seneviratne et al, 2010;Ruosteenoja et al, 2017]. Even so, air humidity has multiple implications in areas with cold climate as well.…”
Section: Introductionmentioning
confidence: 99%